2011
DOI: 10.1007/s00262-011-1072-9
|View full text |Cite
|
Sign up to set email alerts
|

Ab-IL2 fusion proteins mediate NK cell immune synapse formation by polarizing CD25 to the target cell-effector cell interface

Abstract: The huKS-IL2 immunocytokine (IC) consists of IL2 fused to a mAb against EpCAM, while the hu14.18-IL2 IC recognizes the GD2 disialoganglioside. They are under evaluation for treatment of EpCAM+ (ovarian) and GD2+ (neuroblastoma and melanoma) malignancies because of their proven ability to enhance tumor cell killing by antibody-dependent cell-mediated cytotoxicity (ADCC) and by antitumor cytotoxic T cells. Here, we demonstrate that huKS-IL2 and hu14.18-IL2 bind to tumor cells via their antibody components and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 54 publications
(61 reference statements)
1
30
0
Order By: Relevance
“…The impact of hu14.18-IL2 on tumor growth following radiation in FcγR-deficient mice was modest, albeit significant (Figure 3C), yet did not impact animal survival (Figure 3D). This tumor-growth inhibition by IC (but not by mAb) in FcγR-deficient mice may reflect the capacity of hu14.18-IL2 to tether effector cells to tumor cells via IL2 receptors, as previously reported (32). …”
Section: Resultssupporting
confidence: 79%
“…The impact of hu14.18-IL2 on tumor growth following radiation in FcγR-deficient mice was modest, albeit significant (Figure 3C), yet did not impact animal survival (Figure 3D). This tumor-growth inhibition by IC (but not by mAb) in FcγR-deficient mice may reflect the capacity of hu14.18-IL2 to tether effector cells to tumor cells via IL2 receptors, as previously reported (32). …”
Section: Resultssupporting
confidence: 79%
“…Such treatments might also be expected to synergize with any direct therapeutic effect of the antibody mediated by the antibody itself or through interaction with innate effectors such as NK cells that express Fc receptors. Preclinical studies in mice as well as clinical trials in patients with neuroblastoma revealed that T cells and NK cells were important in the anti-tumor effects [70-73]. Interestingly, it appears that therapeutic efficacy of these complete antibody-IL-2 fusions, may not be simply due to enhanced delivery of cytokine to the tumor.…”
Section: Antibody-cytokine Fusionsmentioning
confidence: 99%
“…Interestingly, it appears that therapeutic efficacy of these complete antibody-IL-2 fusions, may not be simply due to enhanced delivery of cytokine to the tumor. Rather, the biological activity of the antibody-IL-2 fusions appears in part to be due to the increased killing of tumor cells as a result of increased conjugate formation due to binding of IL-2 receptors on immune cells [73,74]. Thus in essence, the IL-2 conjugated antibody forms a “bridge” between cytotoxic cells and the target tumor cells.…”
Section: Antibody-cytokine Fusionsmentioning
confidence: 99%
“…Preclinical studies showed that this fusion protein (or immunocytokine) had far superior antitumor activity when compared to comparable doses of ch14.18 mAb and IL-2 given simultaneously as individual agents 101 . A study evaluating immunocytokine-facilitated conjugate formation between NK cells and tumor cells demonstrated that tumor cells coated with immunocytokine were bound to NK cells not only through the Fc region of the immunocytokine but also through the IL-2 moiety 102,103 . NK cells bound to tumor cells formed activated immune synapses, defined by the localization of LFA-1 and CD2, along with clustering of NK cell CD25 into the synapse.…”
Section: Enhancing Nk Cell Function With Monoclonal Antibodiesmentioning
confidence: 99%